2009
DOI: 10.1243/13506501jet642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-pressure hydrogen exposure on wear of polytetrafluoroethylene sliding against stainless steel

Abstract: Mechanical components in hydrogen energy systems, such as a fuel cell vehicle and related infrastructures, will operate in high-purity hydrogen. Especially, some seals and valves in fuel cell vehicles should articulate against metal counterface within a pressurized hydrogen gas. However, the effect of high-pressure hydrogen gas on tribological behaviour of materials used in sliding surfaces has not been identified yet. In this study, unfilled polytetrafluoroethylene (PTFE) pins and 316L austenitic stainless-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Over the past several years, the authors' research group has studied the influences of a hydrogen environment on tribological properties of various materials [1][2][3][4][5][6][7][8]. The studies were motivated by the significance of hydrogen as an energy carrier and the necessity for overcoming its congenital defect, i.e., low energy density in terms of volume.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, the authors' research group has studied the influences of a hydrogen environment on tribological properties of various materials [1][2][3][4][5][6][7][8]. The studies were motivated by the significance of hydrogen as an energy carrier and the necessity for overcoming its congenital defect, i.e., low energy density in terms of volume.…”
Section: Introductionmentioning
confidence: 99%
“…The XPS spectra revealed some differences in chemical compositions in both transfer films and the stainless-steel counterpart surfaces after tests. Using the same test set-up and methodology, Nakashima et al [127,128] examined the wear and friction behavior of PTFE in high-pressure hydrogen (40 MPa) to identify the effect of humidity in gaseous hydrogen [127] and higher hydrogen pressure with longer duration. [128] They observed a lower wear rate for tested unfilled PTFE grades with a higher humidity content in the high-pressure hydrogen.…”
Section: Aging Of Thermoplastics In High-pressure Hydrogenmentioning
confidence: 99%
“…Using the same test set-up and methodology, Nakashima et al [127,128] examined the wear and friction behavior of PTFE in high-pressure hydrogen (40 MPa) to identify the effect of humidity in gaseous hydrogen [127] and higher hydrogen pressure with longer duration. [128] They observed a lower wear rate for tested unfilled PTFE grades with a higher humidity content in the high-pressure hydrogen. [127] A lower wear behavior in high-pressure hydrogen exposed PTFE was monitored compared with tests in air.…”
Section: Aging Of Thermoplastics In High-pressure Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Tribological investigations of polymers and polymer composites in hydrogen gas or liquid are rare, but get growing interest due to the increasing number of hydrogen projects. Since early work carried out by the NASA [4], research has been predominantly made at the Hydrogenius Research Center in Japan [5][6][7] and at BAM [8][9][10][11][12]. Author's previous benchmark of composites in liquid hydrogen (LH 2 ) showed that generally graphite filled polymers have beneficial friction behavior [11] in this condition.…”
Section: Introductionmentioning
confidence: 99%